ANALISIS JABATAN DALAM MANAJEMEN SUMBER DAYA INSANI - Lilik Sofianiyatin; Devi Irmawati (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Employee performance tends to fall short of what is expected between when applying for a job (recruitment) and during the training period. This causes the turnover of employees in the training period. The purpose of this research was conducted to find out the process of job analysis in improving the competence of Human Resources. The method used is a qualitative descriptive research method (Qualitative Descriptive Research), which is a type of research that aims to describe and summarize various conditions and various social phenomena that are the object of research and seek to draw these realities in a certain nature or model. The purpose of this research is to get a picture or description of a problem that exists in a business. From the research results it can be seen that job analysis can play an important role in employee recruitment. An explanation of job analysis on prospective employees, can reveal the obligations that must be carried out before accepting the job